A comparative study of phyllostachys edulis and its dwarf variant phyllostachys edulis ‘Tubaeformis’ at the anatomical, transcriptomic, and DNA methylation levels - Zhenhua, Qiu; Yuanyuan, Sun; Shuyan, Lin; Xinyao, Liu; Long, Li (Frontiers in Plant Science, 2026)
Internode length is an important trait of bamboo and a key indicator affecting the processing and utilization of bamboo materials. Shengyin bamboo is a dwarf variant of Phyllostachys edulis (Moso bamboo) with abnormally shortened internodes, yet its dwarfing mechanism has not been clarified. In this study, we adopted the method of Whole-Genome Bisulfite Sequencing (WGBS) for DNA methylation combined with RNA Sequencing (RNA-seq) to explore the key causes of dwarfism in Shengyin bamboo. Observations via paraffin sections and scanning electron microscopy (SEM) indicate that abnormal cell division and elongation in internodes are the key causes of dwarfism in Shengyin bamboo. Cell division-related genes such as GRF (Growth-regulating factor) and Cyclin are highly expressed during the cell division stage (early growth stage) of Moso bamboo internodes, while genes associated with cell elongation (Expansin-like A, EXPA) are highly expressed during the cell elongation stage (late growth stage) of Moso bamboo internodes. DNA methylation levels exhibit significant differences between Moso bamboo and Shengyin bamboo. Specifically, the DNA methylation level of Moso bamboo at the late stage of internode elongation is higher than that at the early stage, and this difference is significantly greater than the variation observed between the late and early stages of internode elongation in Shengyin bamboo. The expression of most genes shows a negative correlation with promoter methylation levels, indicating that methylation levels inhibit gene expression. Based on transcriptome data, GRF6a, a gene potentially highly expressed in the early stage of internode growth of Moso bamboo under DNA methylation regulation, was screened out. Genetic transformation of rice showed that GRF10 can promote the growth and development of rice internode cells. In summary, under the regulation of DNA methylation, the expression of genes involved in internode cell division and elongation is inhibited, leading to fewer longitudinal cell lengths and cell numbers in the internodes of Shengyin bamboo compared to Moso bamboo, ultimately resulting in the shortened internodes of Shengyin bamboo.